cho 2 đa thức P(x)=x2+2mn+m2
Q(x)=x2+(2m+1)x+m2
tìm m,biết P(1)=Q(-1)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(H\left(-1\right)=K\left(2\right)\Rightarrow-1+3m+m^2=4+2\left(3m+2\right)+m^2\)
\(\Leftrightarrow-1+3m=8+6m\Leftrightarrow3m=-9\Leftrightarrow m=-3\)
Chọn C
Ta có: P(x) + Q(x) = x3+ x2+ 2x-1
⇒ Q(x) = (x3 + x2 + 2x-1) - P(x)
= 2x3 + 4x2 - 8x - 3.
Ta có:
\(P\left(x\right)=x^2+2mx+m^2\)
\(\Leftrightarrow P\left(1\right)=1+2m+m^2\)
\(Q\left(x\right)=x^2+\left(2m+1\right).x+m^2\)
\(\Leftrightarrow Q\left(-1\right)=1-\left(2m+1\right)+m^2=m^2-2m\)
Mà \(P\left(1\right)=Q\left(-1\right)\)
\(\Leftrightarrow1+2m+m^2=m^2-2m\)
\(\Leftrightarrow2m+2m=-1\)
\(\Leftrightarrow4m=-1\)
\(\Leftrightarrow m=\frac{-1}{4}\)
Vậy \(m=\frac{-1}{4}\)
1: P(x)=M(x)+N(x)
=-2x^3+x^2+4x-3+2x^3+x^2-4x-5
=2x^2-8
2: P(x)=0
=>x^2-4=0
=>x=2 hoặc x=-2
3: Q(x)=M(x)-N(x)
=-2x^3+x^2+4x-3-2x^3-x^2+4x+5
=-4x^3+8x+2
a, P(x) = 3x\(^2\) + 2x\(^2\) -2x + 7 - x\(^2\) - x
= \((3x^2+2x^2-x^2)\) + (-2x - x) + 7
= 4x\(^2\) - 3x + 7
Q(x)=-3x\(^3\) + x - 14 - 2x - x\(^2-1\)
= -3x\(^3\) + (x-2x) +(-14-1) - x\(^2\)
= -3x\(^3\) - x - 15 - x\(^2\)
b, N(x)=P(x)-Q(x) =(4x\(^2\)-3x+7)-(-3x-x-15-x)
= 4x\(^2\)-3x+7 + 3x\(^3\)+x+15+x\(^2\)
= (4x\(^2+x^2\)) + (\(-3x+x\))+(7+15)+3x\(^3\)
= \(5x^2\) - 2x + 12 +3x\(^3\)
M(x)=P(x)+Q(x)
=(4x\(^2\)-3x+7)+(-3x\(^3\)-x-15-x\(^2\))
=4x\(^2\)-3x+7-3x\(^3\)-x-15-x\(^2\)
=(4x\(^2\)-\(x^2\)) + (-3x-x) + (7-15)-3x\(^3\)
= 3 \(x^2\) - 4x - 8 -3x\(^3\)
a) Ta có : \(A\left(x\right)=x^2-3x+2=0\)
\(\Leftrightarrow x^2-x-2x+2=0\)
\(\Leftrightarrow\left(x^2-x\right)-\left(2x-2\right)=0\)
\(\Leftrightarrow x\left(x-1\right)-2\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=1\end{matrix}\right.\)